دراسة مواصفات الحمأة الناتجة عن عملية المعالجة البيولوجية بالتهوية المديدة في محطة مرج معيربان - عطية, آمال (Latakia University Journal -Engineering Sciences Series, 2017)
إن تحديد مواصفات الحمأة الناتجة عن عملية معالجة مياه الصرف الصحي له الدور الأساسي في معالجتها والتخلص منها. يهدف هذا البحث إلى دراسة مواصفات الحمأة الناتجة عن محطة مرج معيربان بدراسة عامل المقاومة النوعية للحمأة على الترشيح ( r' )، ولذلك قمنا بأخذ عينات حمأة من المحطة، وأجرينا عليها عدة تجارب مخبرية، وحصلنا على زمن تكثيف الحمأة، ورطوبتها، وتركيز المواد الصلبة فيها، وقمنا بحساب معامل المقاومة النوعية للحمأة على الترشيح عند قيم الرطوبة (97.5 , 95.5 , 94 , 92 , 91 , 88 ) %. أظهرت نتائج البحث انخفاض في قيمة عامل المقاومة النوعية للحمأة على الترشيح بانخفاض رطوبتها، وأن زمن تجفيف الحمأة يستغرق أسبوعين في محطة مرج معيربان.The determination of sludge characteristics of wastewater treatment process has the primary role in the treatment and disposal. This research aims to determine the sludge characteristics by studying specific resistance factor of the sludge on the filtration at Merge Maarban station, so we took samples of sludge from the station and made several laboratory experiments and we got the time of intensify sludge, moisture and The concentration of the solid substances. we calculated specific resistance factor values of the sludge when the moisture values are ( 97.5 , 95.5 , 94 , 92 , 91 , 88 ) %. The research results showed a decrease in resistivity factor value of sludge on the filtration as its moisture become less and the sludge drying time takes tow weeks.